2009
DOI: 10.1211/jpp/61.04.0001
|View full text |Cite
|
Sign up to set email alerts
|

The sacred lotus (<I>Nelumbo nucifera</I>) - phytochemical and therapeutic profile

Abstract: In this review we explore the current pharmaceutical, phytochemical and pharmacological knowledge about this well known plant species as well as several emerging aspects for research on N. nucifera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(64 citation statements)
references
References 47 publications
0
63
0
Order By: Relevance
“…The residue was purified using silica gel column chromatography (hexane/acetone = 3/1 to 2/1) to yield 3 (140.5 mg, 11% from dopamine), an enantiomer mixture that showed m/z 512 [ESI-MS (positive), [M+Na] + ] in the mass spectrum. Since 1 H NMR data of the obtained 3 showed complex signals, probably owing to isomers from benzyl group rotation (rotamer) and chiral carbon (enantiomer), the current and following intermediate products (3)(4)(5) were confirmed only using the mass spectra.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The residue was purified using silica gel column chromatography (hexane/acetone = 3/1 to 2/1) to yield 3 (140.5 mg, 11% from dopamine), an enantiomer mixture that showed m/z 512 [ESI-MS (positive), [M+Na] + ] in the mass spectrum. Since 1 H NMR data of the obtained 3 showed complex signals, probably owing to isomers from benzyl group rotation (rotamer) and chiral carbon (enantiomer), the current and following intermediate products (3)(4)(5) were confirmed only using the mass spectra.…”
Section: Synthesismentioning
confidence: 99%
“…Rhizome, leaf, flower, seed, and all other parts are used to treat vomiting, leprosy, inflammation, skin diseases, neuronal disorders, diarrhea, poisoning, and various other symptoms. 4,5 Many scientific studies have shown the beneficial effects of this plant, including anti-ischaemic, antioxidant, hepatoprotective, antiproliferative, anti-inflammatory, anti-fertility, anti-arrhythmic, anti-fibrosis, antiviral, and other activities. 5,6 Among them, hypoglycemic activity of the plant extract has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and flavonoids, glycosylated flavonols, flavonol, aglycones (myricetin, quercetin, leucocyanidin, rutin, kaempferol, isorhamnetin, astragalin etc.) 90,91 . Neferine (19), a major alkaloid component in N. nucifera embryos, possessed a potent growthinhibitory effect in human osteosarcoma cells, with a mechanism of p21-dependent cell cycle arrest at G1 due to p38 MAPK-mediated p21-stabilizing effect of neferine 91 .…”
Section: Nelumbo Nucifera Willdmentioning
confidence: 99%
“…Major secondary metabolites are alkaloids, flavonoids, and triterpenoids. 18 Neferine, 6, a benzylisoquinoline alkaloid (Figure 1), isolated from the seed embryo of N. nucifera has been reported to block hERG channels stably expressed in human embryonic kidney (HEK293) cells. In whole-cell patch clamp studies, this compound induced a concentration-dependent decrease in hERG current amplitude with an IC 50 of 7.42 μM.…”
Section: ■ Introductionmentioning
confidence: 99%